Loneliness and Well-being among Working, Married and Unmarried Women in Pakistan Mazhar Iqbal , Furkan Ullah Butt, & Akhlaq Ahmad - Bhatti, Mazhar Iqbal (Journal of Peace, Development and Communication, 2021)
This study was set forth to find out the relation of loneliness and wellbeing among working, married and unmarried women in Pakistan. Overall, 210 working, married and unmarried women were recruited for this study through purposive sampling. A self-constructed questionnaire comprising demographic characteristics and loneliness scale Schmidt and Sermat (1983), and wellbeing scale developed by Warwick – Edenbrug (2006) were used to collect the data. Results showed that there is an inverse relationship between loneliness and well-being among working married and unmarried women. Further, the analysis revealed that working unmarried women feel more loneliness and working married women enjoy more wellbeing. All subscales of loneliness confirmed that wellbeing was negatively associated for both working married and unmarried women. It is concluded that loneliness has significant contributor of low wellbeing among unmarried working women. Keywords; Loneliness, Wellbeing, working women, Pakistan